Increased apoptosis of peripheral blood mononuclear cells in patients with perennial allergic asthma/rhinitis: relation to serum markers of apoptosis - Janina Grzegorczyk; Marek L. Kowalski; Anna Pilat; Jolanta Iwaszkiewicz (Mediators of Inflammation)
Background: The goal of our study was to examine spontaneous and stimulated apoptosis of peripheral blood MNC from allergic patients, sensitized to Der p I antigen as compared to cells from non-atopic subjects. Furthermore we aimed to investigate which populations of mononuclear cells (lymphocytes, monocytes) undergo the apoptosis and to determine relations between apoptosis and serum levels of sFas/APO-1, ICE/caspase-1 or TNF-α.